Luciano Freire: between tradition and novelty - Maria da Conceição Lopes Casanova (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
This paper addresses the problematic concerning the restoration of early paintings (primitivos Portugueses) by Luciano Freire, and his role in the Portuguese conservation setting during the first half of the twentieth century. It seeks to describe the national conservation context, with reference to the international scene, highlighting the dominance of humanistic culture, the delay of scientific knowledge, but at the same time, the early functioning of the interdisciplinary team.